1982
DOI: 10.1159/000287565
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic Nausea and Vomiting Associated with Termination of Cancer Chemotherapy

Abstract: Psychogenic (pretreatment) nausea with or without vomiting develops in many patients undergoing chemotherapy for cancer. This phenomenon can be understood as classical aversive conditioning of the gastrointestinal system. Most patients tolerate this side effect of chemotherapy treatment. The author reports 4 patients who were non compliant or discontinued chemotherapy; each patient alleged that the pretreatment symptoms prompted this behavior. Closer examination revealed that these patients avoided chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…response to being actively treated for their illness (Forester et al, 1978). Nausea, vomiting, anorexia and fatigue, are common consequences of radiotherapy during cancer treatment (Forester et al, 1985), but it has been suggested that these symptoms associated with chemotherapy or radiotherapy may be influenced by psychological factors and interventions (Chang, 1981;Morrow and Morrell, 1982;Weddington, 1982;Redd and Andrykowski, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…response to being actively treated for their illness (Forester et al, 1978). Nausea, vomiting, anorexia and fatigue, are common consequences of radiotherapy during cancer treatment (Forester et al, 1985), but it has been suggested that these symptoms associated with chemotherapy or radiotherapy may be influenced by psychological factors and interventions (Chang, 1981;Morrow and Morrell, 1982;Weddington, 1982;Redd and Andrykowski, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence estimates have ranged up to 65% (5) of all chemotherapy patients but it appears that about 25-50% of all patients experience ANV (2)(3)(4). Furthermore, ANV can be both physically and psychologically stressful, compromising quality of life as well as influencing some patients to discontinue chemotherapy (6). Theoretical interest in ANV stems from attempts to understand its etiology.…”
Section: Introductionmentioning
confidence: 99%
“…W. Weddington [35] обратил внимание на то, что у больных лимфогранулематозом, получающих полихимиотерапию, нередко возникает психогенная тошнота, иногда со рвотой. Этот феномен автор объясняет с позиций выработки условного рефлекса, но интерпретирует его с психодинамических позиций («использование» пациентами психогенных симптомов для объяснения избегания химиотерапии).…”
Section: нозогенные реакции и посттравматические стрессовые расстройстваunclassified